2020
DOI: 10.1136/archdischild-2020-318915
|View full text |Cite
|
Sign up to set email alerts
|

Reflexes that impact spontaneous breathing of preterm infants at birth: a narrative review

Abstract: Some neural circuits within infants are not fully developed at birth, especially in preterm infants. Therefore, it is unclear whether reflexes that affect breathing may or may not be activated during the neonatal stabilisation at birth. Both sensory reflexes (eg, tactile stimulation) and non-invasive ventilation (NIV) can promote spontaneous breathing at birth, but the application of NIV can also compromise breathing by inducing facial reflexes that inhibit spontaneous breathing. Applying an interface could pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 81 publications
0
31
0
1
Order By: Relevance
“…Infants born at an early GA have structurally and functionally immature lungs and can be classified according to their ability to breathe spontaneously, which is a major determinant of the level of the required respiratory support. Spontaneous breathing depends on not only lung maturation, but also on the developmental status of the central nervous system and its ability to manage the respiratory drive and the control of respiratory muscles [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants born at an early GA have structurally and functionally immature lungs and can be classified according to their ability to breathe spontaneously, which is a major determinant of the level of the required respiratory support. Spontaneous breathing depends on not only lung maturation, but also on the developmental status of the central nervous system and its ability to manage the respiratory drive and the control of respiratory muscles [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic and extrinsic factors influencing aerosol drug delivery in premature infants. The figure depicts two possible scenarios: (1) nebulizer positioned in the inspiratory limb of a standard constant flow ventilator (top); this nebulizer positioning could also be applied to bubble Continuous Positive Airway Pressure (CPAP) and variable flow drivers, and to High Flow Nasal Cannula (HFNC);(2) nebulizer positioned between the Y piece and the patient interface in a standard constant flow ventilator (bottom); this nebulizer positioning could be compatible with bubble CPAP but not with variable flow drivers nor HFNC…”
mentioning
confidence: 99%
“…Te Pas et al observed a positive effect of the use of repetitive tactile stimulation on respiratory effort and oxygenation of preterm infants at birth (3): rubbing the sole of the foot or the infants'back supposedly activates proprioceptors or somatic/visceral mechanoreceptors in the thorax, respectively, which are known to stimulate spontaneous breathing (3). These afferent somatosensory pathways are functional even before 25 weeks of gestation (4,5). To best of our knowledge, no randomized clinical trials have evaluated the e cacy of early and continued respiratory facilitation physiotherapy in avoiding or reducing the need for invasive respiratory support of preterm infants in NICU.…”
Section: Introductionmentioning
confidence: 99%
“…Te Pas et al observed a positive effect of the use of repetitive tactile stimulation on respiratory effort and oxygenation of preterm infants at birth [ 3 ]: rubbing the sole of the foot or the infants’ back supposedly activates proprioceptors or somatic/visceral mechanoreceptors in the thorax, respectively, which are known to stimulate spontaneous breathing [ 3 ]. These afferent somatosensory pathways are functional even before 25 weeks of gestation [ 4 , 5 ]. To best of our knowledge, no randomized clinical trials have evaluated the efficacy of early and continued respiratory facilitation physiotherapy in avoiding or reducing the need for invasive respiratory support of preterm infants in NICU.…”
Section: Introductionmentioning
confidence: 99%